Osmotic Effect on Human Erythrocyte Detergent Lysis - Markova, K. V.; Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2009)
There was studied the human erythrocyte hemolysis in the media, containing NaCl and sucrose of different molarity under the effect of non-ionic detergents (Tween 20: polyoxyethylene sorbitan monolaurate; Triton X-100: octylphenol polyethylene glycol) and ionic ones (CTAB: cetyl trimethyl ammonium bromide; SDS: sodium dodecyl sulphate) of various concentrations. Their effect on cell lysis in the presence of aggregate state modifier of band 3 protein: DIDS (4,4-diisothiocyanostilbene-2,2-disulfonic acid) was studied. The percentage of erythrocyte hemolysis increases when augmenting detergent concentration in solution. In the solution with 0.15 M NaCl; 0.5 M sucrose; 20 mM Tris (pH 7.4) we fixed the highest cell integrity in the presence of all mentioned detergents. DIDS modifier in the medium strengthens hemolysis in cells, although does not change the tendency of its development in NaCl and sucrosecontaining media in the presence of ionic and non-ionic detergents. The medium, containing 0.15 M NaCl and 0.5 M sucrose was established to provide the erythrocyte resistance to detergents. The intensity of such a protective effect and hemolysis strengthening DIDS effect depends on a detergent type.